Empowerment Of The Walikukun Village Community, Carenang District, Serang Regency, Banten Province, Indonesia Through Agriculture Land Optimization Based On Ecological Economics - Ade Sumiardi; Sev Rahmiyanti; Rustam Effendi (International Journal Of Community Service, 2025)
Ecological Economics has many benefits related to the right to life of organisms, cost and benefit factors, and aesthetic factors for humans. The value of ecological economics is as a protector of the balance of the hydrological cycle and water management, a guardian of soil fertility through the supply of nutrients from forest litter, preventing erosion, abrasion and controlling microclimates. The purpose of activities to increase community independence through optimization of agricultural land based on ecological economics is to realize the active role of the community in increasing food production, maintaining environmental sustainability based on ecological economics so as to increase use value, there is harmony between aspects of use and maintenance, improving aspects of health and community welfare and forming an entrepreneurial spirit. Need Assessment through a survey method approach, socialization, mentoring (workshops, counseling and training), active participation, monitoring and ending with program evaluation is expected to be able to increase community independence regarding the importance of land optimization based on ecological economics. The main programs implemented include community empowerment, increasing production, organizational management, marketing management, facilities and infrastructure and socio-culture. The results obtained are that the community periodically monitors agricultural land based on technology applications, the application of polyculture-based planting patterns to maintain the balance of soil fertility and is active in environmental conservation efforts.